The Effect of Project Based Blended Learning Towards Negotiation Text Writing Ability Moderated by Learning Motivation - Sadieli Telaumbanua (STAI Hubbulwathan Duri, 2022)
This study aims to examine the effect of Project-Based Blended Learning on the ability to write negotiating texts moderated by the role of learning motivation. This experimental study involved 60 students in different classes where 30 people are in the control group and 30 others are in the experimental group. The data in this study are obtained from the results of the pretest and posttest to assess the ability of negotiating texts. The collected data is analyzed using the Anova test. Before being analyzed, the researcher tested the instrument and tested the classical assumptions. The test results show that all instrument items are valid and reliable. All data are known to meet the classical assumption test. The results of hypothesis testing indicate that learning motivation is able to moderate the relationship between project-based blended learning and the ability to write negotiating texts. Teachers are advised to apply project-based blended learning with more intensity to be applied in learning. For further researchers, it is possible to integrate this learning model into learning activities to measure the improvement of other students' abilities.